ANALISIS USAHATANI PEMBIBITAN KARET DI DESA LALANG SEMBAWA KECAMATAN SEMBAWA KABUPATEN BANYUASIN SUMATERA SELATAN (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2019)
This research undertaken to knowthe number of income and profitability in rubber nursery at LalangSembawa Village Sembawa District Banyuasin Regency South Sumatra. The study was conducted in LalangSembawa Village, SembawaSubdistrict, Banyuasin Regency, South Sumatra in June 2019. The sampling method is the slovin method with a critical value of 10%, so that from a population of 67 farmers there are 40 sample farmers. Based on the results of research on rubber nursery farm income in LalangSembawa Village, the conclusions that can be obtained are: 1. The average income for rubber nursery farming in LalangSembawa Village is Rp. 61,945,697 / period of production. 2. R / C of rubber nursery farming in LalangSembawa Village has a value of 5.90 or more than one, this shows that the rubber nursery farming in LalangSembawa Village is profitable and feasible to be cultivated